Some Important Medicinal Trees of District Bijnor - and Ravinder Kumar, Shalu Chaudhary (Recent Research in Science and Technology, 2011)
Bijnor district of Uttar Pradesh (India) has a great heritage and rich in various green and semievergreen species. Till now, very little information exists on the district’s flora in general, and medicinal species found within its limit in particular. Traditional medicine has its own great importance in Indian society. This communication presents information on the traditional uses of thirty trees collected from the various areas of district Bijnor (U.P.). The present study attempted to discern if traditional plant use and availability of important common medicinal plants are maintained in today’s urban environment.